2019
DOI: 10.1186/s42358-018-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathophysiologic relevance of autoantibodies in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune/inflammatory disease affecting 0.5 to 1% of adults worldwide and frequently leads to joint destruction and disability. Early diagnosis and early and effective therapy may prevent joint damage and lead to better long-term results. Therefore, reliable biomarkers and outcome measures are needed. Refinement of the understanding of molecular pathways involved in disease pathogenesis have been achieved by combining knowledge on RA-associated genes, environmental factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 65 publications
(197 reference statements)
1
76
0
1
Order By: Relevance
“…RF and ACPA are autoantibodies locally produced in the inflamed synovium by B cells. Clinical usefulness of these autoantibodies as diagnostic and prognostic factors of disease are now widely accepted (21). Moreover, B cells mediate T-cell activation via the expression of costimulatory molecules and by secreting pro-inflammatory cytokines, particularly TNFα (22).…”
Section: Discussionmentioning
confidence: 99%
“…RF and ACPA are autoantibodies locally produced in the inflamed synovium by B cells. Clinical usefulness of these autoantibodies as diagnostic and prognostic factors of disease are now widely accepted (21). Moreover, B cells mediate T-cell activation via the expression of costimulatory molecules and by secreting pro-inflammatory cytokines, particularly TNFα (22).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that RF is a pathogenic autoantibody that plays a key role in the pathophysiology of RA [56]. In normal conditions, transient production of low-affinity IgM-RF is regularly induced by immune complexes and polyclonal B cell activators, such as bacterial lipopolysaccharide and Epstein-Barr virus [57]. The main role proposed for RF in RA is to form immune complexes, fix complement, and release chemokines, such as C5a, thus recruiting inflammatory cells (neutrophils) into the joints.…”
Section: Rheumatoid Factormentioning
confidence: 99%
“…RF plays a pivotal role in the differential diagnosis and prognosis of RA patients [57]. It has been shown that RF is useful in predicting the development of RA, as the detection of IgM-RF can be used as a marker of inflammatory activity [61].…”
Section: Rheumatoid Factormentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic autoimmune disease, with a reported prevalence ranging between 0.5–1% worldwide [ 1 , 2 , 3 ]. RA is characterized by a systemic auto-immune disease, causing joint pain, swelling, and stiffness.…”
Section: Introductionmentioning
confidence: 99%